(untitled) (Baghdad Science Journal, 2019)
baumannii is an aerobic gram negative coccobacilli, it is considered multidrug resistance pathogen (MDR) and causes several infections that are difficult to treat. This study is aims to employ physical methods in sterilization and inactivation of A. baumannii, as an alternative way to reduce the using of drugs and antibiotics. Cold Atmospheric Plasma was generated by one electrode at 20KV, 4 power supply and distance between electrode and sample was fixed on 1mm. A. baumannii (ATCC 19704 and HHR1) were exposed to Dielectric Barrier Discharge type of Cold Atmospheric Plasma (DBD-CAP) for several periods of time (15, 30, 45, and 60 sec.) . After sterilization test, several methods were done to analyze the effect of DBD-CAP on bacterial morphology, proteins and DNA. Change in morphology was assessed by cover slid method. Damaged DNA was investigated by PCR technique, and DNA sequencing. The impact of DBD-CAP on the entity of proteins was detected by SDS-PAGE. The observed inactivation of bacterial colony on agar plates has been quantified by measuring the inactivation diameter. The important conclusion that HHR1 more resistance to DBD-CAP than ATCC 17904 because it is more virulence than standard strain; thus, the growth of both strains is largely affected by plasma and this influence is increased by increasing the time of exposure, also the plasma affects the DNA especially on standard strain as it is explained in sequencing result, so it causes more deletion in DNA sequence. In addition, plasma also has been showed to damage proteins and morphology thus, the bacterial cells transform from cocco-bacillus to bacillus.